Fans identification: the bright side of football sponsorship effectiveness - Silva, A. (2021)
Football events are by far one of the most preferred leisure activities amongst fans around the world, namely when it involves their favorite team. The measurement of sponsorship results is seen as a research priority, however, some results found are not consistent, in which mediation is seen as a research priority. This research intends to: i) determine fan identification effect on perceived congruency between sponsor and sponsored team, and on intentions towards buying sponsor’s products, and; ii) determine the mediation role of perceived congruence. In total, 1,399 fans from a top three Portuguese professional football team were considered for analysis. For statistical analysis, Structural Equation Modeling was used. Results show that higher levels of fans’ team identification lead to higher intention to buy sponsor’s products, and the most innovative result was the relevant mediating role of the perceived congruence in the formation of the purchase intention on sponsor’s products.